Institutional obstacles for the implementation of a River Basin Management concept in Western Ukraine - Nina Hagemann (Helmholtz-Zentrum für Umweltforschung (UFZ), 2012)
This paper provides results from a case study in Western Ukraine where a River Basin Management (RBM) concept for the Western Bug River has been initiated. Ukraine aims at the introduction of an integrated water resources management implemented through a river basin organizational structure based on the principles of the EU Water Framework Directive (WFD). Even though the implementation process has been initiated for the Western Bug River catchment the process came to halt. The paper aims at outlining the structural deficits that hinder a successful implementation of a RBM concept in the case study area. The results show that in Ukraine - a country still in transition - the institutional structure is not well enough established to organize a process that calls for new institutions and governance structures that challenges even industrialized countries. More precisely, the challenges for Ukraine lie within the inconsistency of the institutional framework that is made explicit when looking at the decentralization process that has been initiated right after independence but is not yet concluded.
Keywords: 330; Transition countries; Ukraine; River Basin Management; Decentralization